Regional Languages at the Brink: Conservation Efforts for Indonesia's 700+ Endangered Languages - Muhammad Nurahmad; Nurasia Natsir (International Journal of Educational Research, 2026)
Indonesia harbors extraordinary linguistic diversity with over 700 regional languages representing approximately 10% of the world's languages within 1.3% of global land area. However, this diversity faces existential threat from language shift toward Indonesian, urbanization, education policies favoring the national language, and globalization. UNESCO classifies 146 Indonesian languages as endangered, with several dozen facing imminent extinction as last speakers age without intergenerational transmission. This study documents the current vitality status of Indonesian regional languages, analyzes factors driving language endangerment and shift, evaluates existing conservation efforts, and proposes evidence-based strategies for language revitalization and maintenance. A multi-phase approach was employed: vitality assessment of 150 regional languages using UNESCO's Language Vitality and Endangerment framework with surveys involving 2,400 speakers; ethnographic case studies in 12 speech communities; policy analysis; evaluation of 25 revitalization programs; and predictive modeling of language shift trajectories. Of 150 surveyed languages, only 23 (15.3%) classified as safe with robust intergenerational transmission; 48 (32.0%) were vulnerable; 42 (28.0%) definitely endangered; 28 (18.7%) severely endangered; and 9 (6.0%) critically endangered. Key endangerment drivers included Indonesian-only education (92.3% of schools), urban migration (67.8% of youth), negative language attitudes (54.2% of parents), and lack of written traditions (73.4% of languages lacking orthographies). Modeling projected that without intervention, 40% of currently vulnerable languages will become definitely endangered within 20 years. Successful revitalization demands community-owned interventions, mother-tongue-based multilingual education, new digital language domains, and attitude change campaigns. Indonesia's linguistic diversity represents invaluable cultural and scientific heritage requiring urgent, coordinated conservation action.